Answer:
(x, y) = (2, 28.8)
Explanation:
Your ability to do arithmetic should not be limited to integers. Here we see the coefficients of y are related by a factor of -5, so multiplying the first equation by 5 can make the y-terms cancel when that is added to the second equation.
5(1.3x +0.5y) +(-0.7x -2.5y) = 5(17) +(-73.4)
6.5x +2.5y -0.7x -2.5y = 85 -73.4 . . . . . eliminate parentheses
5.8x = 11.6 . . . . . . collect terms
x = 11.6/5.8 = 2 . . . . . . . divide by the coefficient of x
1.3(2) +0.5y = 17 . . . . . . substitute for x in the first equation
0.5y = 14.4 . . . . . . subtract 2.6
y = 28.8 . . . . . . . . multiply by 2
The solution is (x, y) = (2, 28.8).